Alopecia Areata vs Trichotillomania. Differential Diagnosis According to Trichoscopy - Aida G. Gadzhigoroeva ("Paediatrician" Publishers LLC, 2020)
Alopecia areata is one of the most common forms of hair loss in children. Meantime, its clinical picture is similar to trichotillomania, thus, it leads to incorrect diagnosis and management. The article provides major differential diagnosis signs for these related forms of alopecia and describes in details trichoscopic features of alopecia areata and trichotillomania.